(untitled) (Global Journal of Human-Social Science, 2020)
Menstruation is a sensitive issue in socio-cultural settings, still now discussing about it publicly is treated as secrecy and embarrassment, and introduced it as unclean to girls. Part of purity, girls, are not allowed to perform religious prayer or worship, including touching books, material, and even visiting places associated with religious beliefs. But now, in a greater extent, television advertisement as an agent of socialization, socialize to girls and women by conveying information and promoting awareness about menstruation and hygiene management; including using a sanitary napkin, how to use and duration of carrying a pad, and so on by breaking down menstrual taboos to normalize it to all. The objective of this research is to explore the way menstruation, and hygiene-related information is presented on television advertisement; how contextual factors contribute to maintaining menstrual hygiene; and to overcome hygiene-related problems that are encountered by college girls during menstruation. As the study is descriptive, here an amalgamation of quantitative and qualitative methods applied to address research objectives.